Identification of the Key Characteristics of Daughter-Father Avoidant Attachment - Nikolić, Marija; Krstić, Ksenija (Psihološka istraživanja, 2023)
The paper deals with the daughter-father avoidant attachment. The purpose of the study is to identify the characteristics, relationships and behaviour of fathers that are perceived by the daughters as the key ones for the formation of avoidant attachment with fathers. Bearing this in mind, the study focuses on youth who have a combination of two patterns, secure attachment to the mother and avoidant attachment to the father. The research was designed as a mixed-method study. In the first phase, 233 young people aged 15 to 35 (73.1% women) were included and the Experience in Close Relationships Scale was administered. From this sample, we then selected the participants (N=49, 73.6% women, Mage=20.9) who had a combination of secure attachment to the mother and avoidant attachment to the father. The final sample in the second, qualitative phase of the research consisted of nine girls who accepted to be interviewed. The data were collected through a semi-structured interview based on the AAI and analysed through Interpretative Phenomenological Analysis. The results point to three identified topics common to experiences of all nine participants. The topics relate to the consequences of fathers’ physical absence during the period of growing up of their daughters, the consequences of the lack of two-way communication within the father-daughter interaction, as well as to the daughters’ feeling that the father is a person in whose presence they cannot act freely and naturally in the way they can act in the presence of the mother, to whomthey are securely attached.